Effectiveness of Vaccines and Barriers Against Effective Cold Chain Systems - Osadolor, Owens O; Osadolor, Obehi O; Osadolor, Aisosa J; Ekpeti, Azuka P (Mediscope, 2023)
Vaccination is often considered a cost-effective strategy for the prevention and control of most infectious diseases or vaccine-preventable diseases. Poverty, ignorance, cultural belief and practices, locality of residence, level of awareness on vaccine safety and lack of access to health care facilities are among the obstacles to vaccination leading to low vaccine coverage. Low vaccine coverage among young children across remote and rural areas, slums and riverine areas is not a reflection of the health and social-related Sustainable Development Goals. Poor handling of vaccines has been identified as one of the reasons for the reduction in vaccine effectiveness at the time of administration. Cold chain is the system of transporting, storing and distributing vaccines in a viable state at the recommended temperature from the point of manufacture to the point of use. Some factors contributing to the weakness of the cold chain are delays during transportation, quality of refrigerators, method of storage, period of storage at the health facility, improper use of refrigerators, equipment breakage, lack of trained personnel capable of managing the cold chain, unreliable power sources and limited resources (material, financial, and human). Mediscope 2023;10(1): 38-41